Life History and Damage by Systena frontalis F. (Coleoptera: Chrysomelidae) on Vaccinium macrocarpon Ait. Issue 1 (9th February 2021) - Jaffe, Benjamin D; Rink, Stephanie; Guédot, Christelle
Abstract: Pest management of emerging pests can be challenging because very little fundamental knowledge is available to inform management strategies. One such pest, the red-headed flea beetle Systena frontalis (Fabricius) (Coleoptera: Chrysomelidae), is increasingly being identified as a pest of concern in cranberries Vaccinium macrocarpon Aiton (Ericales: Ericaceae). To improve our understanding of this pest and to develop more targeted management programs, we conducted field and laboratory studies to characterize the development, seasonal emergence patterns, and density-dependent plant injury. We found that significantly more flea beetle eggs hatched when exposed to sustained cold treatment between 0 and 5°C for 15 wk than at warmer temperatures, and for shorter and longer cold-period durations. The adults emerged sporadically over the summer, were patchily distributed, fed on both fruit and foliage, and preferentially fed on new plant growth. Using soil cores, we found eggs and larvae located relatively deep (>30 cm) in the soil. These patterns indicate that S. frontalis likely overwinters as eggs, and that targeting the larval stage may be the most effective management approach. Despite the cryptic nature of the larvae, continuing to improve our understanding of this life stage will be critical to optimizing control strategies.